Different true-protein sources do not modify the metabolism of crossbred Bos taurus x Bos indicus growing heifers - Mota, Diego Azevedo; Messana, Juliana Duarte; Canesin, Roberta Carrilho; Fiorentini, Giovani; Pires, Alexandre Vaz; Berchielli, Telma Teresinha [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2015)
The present study was conducted to investigate the effect of alternative true-protein sources to soybean meal, with different ruminal degradability, using a sugarcane-based diet, on nutrient digestion, ruminal fermentation, efficiency of microbial protein synthesis and passage rate in prepubertal dairy heifers. Eight crossbred rumen-and duodenum-cannulated Holstein x Gyr dairy heifers (202.0 +/- 11.5 kg BW) were evaluated in a 4 x 4 Latin square experimental design with four treatments and four periods in two simultaneous replicates. Dietary treatments were: soybean meal; cottonseed meal; peanut meal; and sunflower meal. When associated with diets containing sugarcane, the different protein sources did not affect intake or digestibility of dry mater, crude protein, organic matter and neutral detergent fiber. The average ruminal pH, NH3-N and concentration of total volatile fatty acids were not different among the diets supplied. The concentration of butyric acid was different among the protein sources, wherein the animals fed the diet with sunflower meal presented lower values than those fed the other sources. Diets did not affect nitrogen balance, microbial nitrogen, microbial synthesis efficiency, estimated dry matter flow, or passage rate. Alternative protein sources can be used to reduce the costs without changing the animal metabolism.
Keywords: Microbial synthesis; Nitrogen balance; Rumen degradable protein; Sugarcane